THE EFFECTIVENESS Of STAD (STUDENT TEAM ACHIEVEMENT DIVISION) AND ICT TECHNIQUE in INCREASING READING COMPREHENSION of RECOUNT TEXT FOR EIGHT GRADE STUDENTS At JUNIOR HIGH SCHOOL - Siti Nafi’yah (JURNAL KOULUTUS, 2018)
The research focuses on reading comprehension used in recount text at junior high school. Reading is a part of skill english. It is concerning to increase reading comprehension at junior high school. Starting for Eight Grade Students at junior high school. The research problems of the study are (1) Do the students who have been taught recount text with student team achievement divisions (STAD) technique is achieve better than using Information and communication technology (ICT) ? (2) What are students’ opinion toward the implementation of student team achievement divisions (STAD) and Information and communication technology (ICT) technique in teaching reading recount text ?. The purpose of the research are finding (1) To find out wether the students who have been taught STAD technique is significantly better in reading recount text than ICT. (2) To describe the students’ opinions toward the implementation of student team achievement divisions (STAD) and Information and communication technology (ICT) in teaching reading recount text .This design of the study is quasy experimental research design. The source of data was recount text at junior high school of MTSN Karangrejo. The subject of data was junior high school students and the writer chose recount text used in junior high school at eight grade as object of this research. The researcher gave pre test-treatment-post test.The research have used statistic. It was ANCOVA. The researcher showed that mean of STAD group is 82, median is 84 and mode is 80. The std. Deviation is 5,261. The range STAD group is 24. The minimum score in post test of STAD group is 68, the score for maximum of STAD group is 92 . Summary score for post-test of STAD group is 2968. And the researcher found that mean post-test of ICT group is 73,37 and the median score in post-test of ICT group is 76,00. The mode is 76. The std. Deviation is 8,122. The range is 44. The minimum score for post-test of ICT group is 56. The maximum score is 100. The Summary score for post-test of ICT group is 2788. The result of the computation of spss 15 version is , Determine the level of significance, here is 0,00 . Determine the degree of freedom (df) is 72. And determine the critical T-value is 5,635. T value is 5,635 while the significant is 0, 00. It means that there is significant is less than 1 %. So, it can conclude that there is significant different between STAD technique and ICT technique in increasing reading comprehension for junior high school. it can be concluded that ha is accepted.